2020
DOI: 10.1021/acsami.9b20433
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin MoS2 Nanosheets Encapsulated in Hollow Carbon Spheres: A Case of a Dielectric Absorber with Optimized Impedance for Efficient Microwave Absorption

Abstract: A dielectric loss-type electromagnetic wave (EMW) absorber, especially over a broad frequency range, is important yet challenging. As the most typical dielectric attenuation absorber, carbon-based nanostructures were highly pursued and studied. However, their poor impedance-matching issues still exist. Here, to further optimize dielectric properties and enhance reflection loss, ultrathin MoS2 nanosheets encapsulated in hollow carbon spheres (MoS2@HCS) were prepared via a facile template method. The diameter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(58 citation statements)
references
References 71 publications
1
57
0
Order By: Relevance
“…Moreover, the miniaturization and integration of electronic circuits and components put forward the request of flexible portable microwave absorption electronic devices [5,6]. Two-dimension (2D) materials, such as reduced graphene oxide (RGO) [7][8][9][10], MoS 2 [11][12][13][14][15], and new member Mxene [16][17][18][19], are usually applied as microwave absorber owing to their high specific surface area and abundant functional groups as well as defects, which will enhance the propagation paths of incident electromagnetic wave (EMW) inside absorbers by scattering effect and increase the loss through polarization relaxation loss. As one of the 2D material, MoS 2 has adjustable electrical property and can change between insulators and semiconductor metals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the miniaturization and integration of electronic circuits and components put forward the request of flexible portable microwave absorption electronic devices [5,6]. Two-dimension (2D) materials, such as reduced graphene oxide (RGO) [7][8][9][10], MoS 2 [11][12][13][14][15], and new member Mxene [16][17][18][19], are usually applied as microwave absorber owing to their high specific surface area and abundant functional groups as well as defects, which will enhance the propagation paths of incident electromagnetic wave (EMW) inside absorbers by scattering effect and increase the loss through polarization relaxation loss. As one of the 2D material, MoS 2 has adjustable electrical property and can change between insulators and semiconductor metals.…”
Section: Introductionmentioning
confidence: 99%
“…Development of hollow structured materials has been regard as an attractive solution to solve high density issue of materials. [19][20][21] As an attractive micro/nanostructure, multi-shelled hollow spheres (MSHS) have aroused extensive attention due to its unique features such as lightweight, controllable shell numbers and thickness, shell porosity, and intershell spacing. [22][23][24][25][26][27] It can be foreseen that this peculiar structure is favorable for promoting the EM wave absorption performance by following aspects: 1) the multiple shells would lead to the multiple reflections when incident EM wave propagates in the cavities between two adjacent shells; 2) the abundant interfaces generated on the shell-air-shell could boost the interfacial polarization; 3) due to the existence of multiple cavities in this structure, its low density and lightweight features can precisely circumvent density issue of MCo 2 O 4 -based EM wave absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…A high performance MW absorber apart from having strong absorption and wide effective absorption bandwidth (EAB) i.e. the frequency range having RL < -10 dB, should also have lightweight, good thermal stability and ability to tune MW absorption for desired frequency bands 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…A two-dimensional transition metal dichalcogenide, molybdenum disulphide (MoS 2 ), has emerged as a new class of microwave absorbing material in recent years due to its large specific surface area and high dielectric properties [1][2][3][4] . 2D MoS 2 nanosheets prepared by Ning et al 5 using top down exfoliation method reported maximum reflection loss (RL max ) = -38.42 dB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation